(7x+3)+(4x+1)=65

Simple and best practice solution for (7x+3)+(4x+1)=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+3)+(4x+1)=65 equation:


Simplifying
(7x + 3) + (4x + 1) = 65

Reorder the terms:
(3 + 7x) + (4x + 1) = 65

Remove parenthesis around (3 + 7x)
3 + 7x + (4x + 1) = 65

Reorder the terms:
3 + 7x + (1 + 4x) = 65

Remove parenthesis around (1 + 4x)
3 + 7x + 1 + 4x = 65

Reorder the terms:
3 + 1 + 7x + 4x = 65

Combine like terms: 3 + 1 = 4
4 + 7x + 4x = 65

Combine like terms: 7x + 4x = 11x
4 + 11x = 65

Solving
4 + 11x = 65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 11x = 65 + -4

Combine like terms: 4 + -4 = 0
0 + 11x = 65 + -4
11x = 65 + -4

Combine like terms: 65 + -4 = 61
11x = 61

Divide each side by '11'.
x = 5.545454545

Simplifying
x = 5.545454545

See similar equations:

| -10+-53x+-59x^2+14x^3=0 | | 170=-10x | | 4.1=-4+x | | 3p+2p=15 | | 2x-3+x^2=0 | | (n-2)180=3780 | | 3y=5y+18 | | 109=-6(-3m+1)+5 | | 3x=-5-8 | | 4/3y=1 | | 5k-7=4k | | -37(x-74)=x+(-38) | | 3.5t-9.1=8.05 | | -x+2y=2.5 | | 25d+25.4= | | 3.6t+4.93=-30.71 | | 39+6=99+8 | | -27=8m-5m | | 4000=1920*x*8 | | 2m+2.6= | | 1.4m+9.91=-0.87 | | 24x-94=x-10 | | -9r+10=8+3r | | 10-5(9n-9)=10 | | 4x^2-x-29=0 | | 5/20=9/x | | 18a^2-48a+32=0 | | x+-5=2x+1 | | -3(2x+7)=-6x-21 | | 1.5(m-3)=12 | | 2x+y=3.5 | | 3secx-5=-8 |

Equations solver categories